17 An after-action review for adoption of emerging technologies during the COVID-19 pandemic. (15th December 2021) - Visram, Sheena; Toft, Alison; Molyneux, Gemma; Conner, Sue; Sridharan, Shankar; Rogers, Yvonne; Sebire, Neil J
Abstract : Introduction: The COVID-19 pandemic response has accelerated adoption of digital health technologies to support social distancing. In part, this involves repurposing technologies that were not originally developed for healthcare application. In the hospital setting, this includes the appropriation of 'Off the Shelf' (OTS) digital products that facilitate video-based clinical consultations, diagnostics and communication during ward rounds and multi-disciplinary team meetings. Such technologies were implemented within weeks at GOSH where video consultations were implemented for >90% of outpatient appointments. Methods: Here we present the findings from a Debrief-After Action Review (AAR) lasting two hours, supplemented with speculative questions on how lessons learned from the rapid deployment of one technology could inform the adoption practices of other emerging technologies. Results: Fifteen participants, who were members of a Transforming Care Links working group and interested in the impact of digital systems on patient care, contributed to the AAR. Five themes were identified from thematic analysis of this bottom-up approach: (i) Clinical: Planning and redesigning workflows with clear purpose, intent, and communication with clinical teams (ii) Technology: Infrastructure and equipment available across the team based on the needs of the workspace, with security and governance processes (iii) Capability mapping: Building core capability in a structured way across the entire team with space and time to trial out technologies as part of a progressive learning path and supported by clinical champions (iv) Benefits: Demonstrable benefits with new technology enabled ways of working based on preliminary small-scale deployments that deliver measurable value (v) Environment and Context: Context-specific workflow redesign for technology enabled interactions that consider optimum conditions of the physical environment. Conclusion: This user-centred approach identified routine training pathways, equity of access to training opportunities and equipment, a period of trialability and demonstrable benefits as enablers for the successful adoption of emerging technologies.